2020
DOI: 10.1148/radiol.2019191169
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Limb Lymphatic Drainage Pathways and Lymph Nodes: A CT Lymphangiography Cadaver Study

Abstract: I maging of the lymphatic vessels is an essential tool for diagnostic assessment of lymphedema. Lymphoscintigraphy is the current reference standard for lymphatic imaging (1-3). SPECT (4), indocyanine green (ICG) fluorescent lymphography (5-7), and MR lymphography (8) are emerging techniques. Lymphatic imaging of the lower limb requires intradermal or subcutaneous injection of tracer or contrast material in the foot to demonstrate the lymphatic vessels. No standard protocol exists, and single or multiple injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…However, this approach does not always allow visualization of complete lower leg lymphatics. Shinaoka et al [6] reported that injection into this web space demonstrates lymphatic vessels only in the anteromedial group. The anteromedial and posteromedial groups did overlap in the leg; however, the anterolateral and posterolateral groups were independent.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, this approach does not always allow visualization of complete lower leg lymphatics. Shinaoka et al [6] reported that injection into this web space demonstrates lymphatic vessels only in the anteromedial group. The anteromedial and posteromedial groups did overlap in the leg; however, the anterolateral and posterolateral groups were independent.…”
Section: Discussionmentioning
confidence: 97%
“…The intranodal approach has recently been introduced and remarkably reduced time and effort compared with the conventional pedal lymphangiography approach [3][4][5]. However, intranodal lymphangiography cannot be performed at the below-theknee level because the lowest lymph node is present in the popliteal area [6].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we began to propose one additional injection at the root of the limb[s] to our patients. We were aware that one single injection could not reveal all LNs draining to the root of the edematous limb [ 13 ], but our intradermal injection in the lateral part of the thigh in front of the greater trochanter was chosen because we wished 1] to force with such intradermal injection [better than one subcutaneous one] [ 14 ] the quick demonstration a] of the presence of the most frequently expected lymphatic drainages toward unrecognized LNs at the level of the root of the limb[s] and/or in the abdomen and/or b] of possible posterior and/or lateral collateral lymphatic pathways at the level of the pelvis but also 2] to avoid or limit the possible “stardust” effect that might mask some LNs and/or draining LVs.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we began to propose one additional injection at the root of the limb[s] to our patients. We were aware that one single injection could not reveal all LNs draining to the root of the edematous limb [13], but our intradermal injection in the lateral part of the thigh in…”
Section: Plos Onementioning
confidence: 95%
“…The superficial inguinal lymph nodes are further classified into five subgroups by the greater saphenous vein (GSV) and a horizontal line running through the saphenofemoral junction ( Figure 2 ). The five subgroups include superomedial, superolateral, inferomedial, inferolateral, and central groups [ 3 , 13 ]. The superomedial group drains the medial infraumbilical abdominal wall, medial gluteal region, external genitalia, lower anal canal, and the perianal region.…”
Section: Microscopic Anatomy and Physiology Of The Lymphatic Systemmentioning
confidence: 99%